Life cycle approach as a tool for assessing municipal biowaste treatment units A systematic review - Serafini, Laís Fabiana (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2025)
Biowaste is an increasingly relevant environmental issue worldwide, causing significant environmental, economic and social impacts. Effective strategies are crucial to mitigate impacts, maximising biowaste's valorisation. This article presents a systematic literature review on using life cycle assessment (LCA) to evaluate municipal biowaste treatment facilities. The primary objective was to analyse how LCA is applied to assess the environmental efficiency of mechanical and biological treatment involving composting and anaerobic digestion (AD)-based systems. The article addressed the methodological heterogeneity across previous LCA studies, identifying critical gaps and challenges regarding standardisation and result comparability. It underscores the importance of accurately considering environmental indicators and emission factors, as these significantly affect overall LCA outcomes. Results show that most publications focus on Europe and Asia, highlighting a research gap in regions like Africa. The organic fraction municipal solid waste is the predominant feedstock, and 1 tonne of biowaste was the frequently used functional unit, reflecting the upstream impacts of waste. The most recurrent system boundary was the cradle-to-grave, offering a comprehensive analysis as it covers all stages of biowaste treatment from collection to disposal. The studies highlight the environmental benefits of AD-based systems through energy production compensations, particularly in reducing global warming potential, compared with other treatment operations such as landfills. While replacing mineral fertilisers with digestate and compost is very well discussed, it raises concerns about heavy metal content and nutrient availability. Therefore, selective collection of organic waste is crucial to improve compost quality and AD efficiency, though it increases transportation costs